Bayesian optimization of proton generation in terawatt laser–CH2 cluster interactions within a plasma channel - Kim, Artem; Botton, Mordechai; Zigler, Arie (Frontiers in Physics, 2024)
Improving the energy efficiency in generating high-energy proton or boron ions is crucial for advancing the feasibility of neutronless laser-based proton–boron (p-B11) fusion reactions. The primary objective of this work is to optimize the fusion energy efficiency of a proposed advanced p-B11 fusion scheme. In the proposed scheme, an ultrashort laser pulse is guided by a plasma channel filled with carbon–hydrogen (CH2) clusters. The MeV protons are generated by the Coulomb explosion (CE) of the cluster, which, therefore, interact with surrounding boron to produce alpha particles. To evaluate the fusion energy efficiency under various conditions, 2D particle-in-cell (PIC) simulations are used, supplemented with analytical calculations and estimations. The Bayesian optimization (BO) algorithm is utilized to optimize the key interaction parameters. The BO approach allows us to identify optimal cluster and laser parameters that would have higher fusion energy efficiency.